APPROBATION OF FUEL CATALYSTS FOR AIRCRAFT ENGINES - Kozlov, Volodymyr; Volianska, Larysa; Omelianenko, Serhiy; Yakushenko, Оleksander; Flokos, Mark (Proceedings of National Aviation University (archive), 2021)
A study of the impact of fuel catalysts of the Ukrainian company "Auto-Eco-Titan", which were previously tested on reciprocating internal combustion engines of various modes of transport (road, rail, maritime) and showed a significant improvement in technical, economic and environmental performance. The possibility of using these catalysts in gas turbine aviation has been studied on aircraft gas turbine engines.